Efeitos da inundação da Usina Hidrelétrica de Santo Antônio sobre a assembleia de pequenos mamíferos não voadores no alto Rio Madeira - Araujo, Raylenne da Silva (Instituto Nacional de Pesquisas da Amazônia - INPA, 2023)
Due to its invaluable biodiversity and economic potential, the Amazon rainforest is one of the most observed biomes in the world due to its vast territory and abundance of natural resources. However, the Amazon has also been the target of significant human actions, which have threatened the forest's survival and the well-being of human and fauna populations. The implementation of hydroelectric power plants throughout the Amazon has been indicated as one of these anthropogenic impacts, raising an alert about the need to preserve natural areas while pursuing the economic growth planned by local governments. In this thesis, I assess how the implementation of a hydroelectric power plant in the southeastern Amazon affected assemblies of non-flying small mammals over time and space. In Chapter I, I and my coauthors sought to predict how the assembly of small mammals would be affected after the loss of part of the environmental gradient due to flooding caused by a hydroelectric power plant, and how these species were spatially structured according to some environmental variables expected to affect small-mammal species. In Chapter II, we compared some indices of taxonomic diversity, phylogenetics, and functional traits of non-flying small mammals between different sampling periods through data collected before and after the filling of the hydroelectric reservoir. Assemblies of small mammals were distributed differently between areas predicted to be flooded and areas above the planned reservoir. The species were directly related to environmental factors such as soil, vegetation, and distance from the water body, but species present in low areas were also observed in areas individuals in areas expected to be inundated with the filling of the reservoir were eliminated, there would be no loss of species or evolutionary lineages. The number of species, abundance, and frequency of functional traits increased after reservoir filling, followed by a decrease in most of these parameters in the last year of sampling. This thesis contributes to the understanding of ecological processes of non-flying small mammals evaluated through different diversity metrics, and how the use of run-of-the-river dams might interfere with the dynamics of terrestrial species in this tropical region. It hopes that the results presented here will bring greater understanding of Amazonian biodiversity, foster new ecological studies, and serve as basis for improving environmental-impact-assessment techniques.
Keywords: Reservatório hidrelétrico; Perda de habitat; Avaliação de impacto